Meningkatkan Hasil Belajar Peserta Didik Melalui Model Pembelajaran Problem Based Learning Berbantuan Media Wordwall Mata Pelajaran IPAS Kelas VI-A SDN Jajar Tunggal III/452 Surabaya - Evelyn Olyvia Putri; Desi Eka Pratiwi; Endang Sulistiya Wati (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This study endeavors to enhance the scientific learning results of sixth graders at SDN Jajar Tunggal III/452 Surabaya by using the Problem Based Learning pedagogical approach with the support of wordwall media, with a focus on global Indonesian cultural heritage materials. Two rounds of classroom action research have been conducted. Class VI-A students from SDN Jajar Tunggal III/452 Surabaya in the 2024–2025 school year were the focus of this investigation. This study use (1) as its method of data collecting. Second observation. Recordings, three. Interview. The proportion of classical student learning outcomes that fell into the "very low" category was 32.14% before the cycle began, 67.85% during the first cycle, and 100% during the second cycle. Compared to the first cycle's assessment, the second cycle's outcomes were better. With an average final score of 85.55, the assessment findings for cycle II of classical learning completion attained 100%. The results show that in the 2024–2025 school year, students in class VI–A at SDN Jajar Tunggal III/452 Surabaya may benefit from using the problem-based learning approach with wordwall medium to study world-class Indonesian cultural heritage.